Statistical properties of a dissipative kicked system: Critical exponents and scaling invariance - Oliveira, Diego F. M.; Robnik, Marko; Leonel, Edson Denis [UNESP] (Elsevier B.V., 2012)
A new universal empirical function that depends on a single critical exponent (acceleration exponent) is proposed to describe the scaling behavior in a dissipative kicked rotator. The scaling formalism is used to describe two regimes of dissipation: (i) strong dissipation and (ii) weak dissipation. For case (i) the model exhibits a route to chaos known as period doubling and the Feigenbaum constant along the bifurcations is obtained. When weak dissipation is considered the average action as well as its standard deviation are described using scaling arguments with critical exponents. The universal empirical function describes remarkably well a phase transition from limited to unlimited growth of the average action. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Scaling; Standard map; Dissipation